Evaluation of alcohol and substance use in patients with bipolar disorders who presented to a psychiatry outpatient clinic - Tekin Uludağ, Yasemin; Güleç, Gülcan (Journal of Dependence, 2015)
Objective: This study aimed to investigate the rate of psychotropic substance use and determine the types of substances used among patients diagnosed with bipolar disorders who presented at our psychiatric outpatient clinic, and compare the socio-demographic and clinical characteristics of substance users and non-users. Method: 100 patients who consecutively presented themselves to our psychiatry clinic and were diagnosed with Bipolar Disorder according to their DSM-IV criteria were recruited to participate in the study. Individual interviews were conducted with each of the study participants. The Substance Abuse Disorder (SUD) section of the SCID-I interview form, which was created in accordance with DSM-IV criteria, was used to determine the existence of substance abuse disorder. Patients with prior or current use of alcohol, nicotine, or other substances, and those with alcohol-substance abuse disorder according to DSM diagnosis criteria, were identified. Results: 60% of the Bipolar Disorder patients enrolled in this study had used cigarettes at some time in their life, and 51% were current cigarette smokers. 34% of the participants had used alcohol at some time in their life, 24 of whom were social drinkers and 10 were identified with alcohol use disorder. Seven participants were found to have a history of substance abuse other than alcohol or nicotine. The rate of patients with current alcohol use disorder was 3% and current substance abuse disorder other than alcohol or nicotine was 2%. 14% of participants in our study were found to have had alcohol-substance abuse disorder at some time in their life. Conclusion: In Turkey, alcohol-substance use prevalence in patients with bipolar disorders is lower than other counties. There have been very few local studies investigating the prevalence of substance use in patients with Bipolar Disorder, so we believe that this study will contribute to the literature on the subject.